Design of an integrated quality management system for Colombian higher education academic programs (2021)
In this research study an integrated quality management system is proposed for academic programs in Colombian higher education by considering the Colombian legal requirements and high quality accreditation guidelines, and the ISO 9001 standard. Concepts associated with high quality assurance, quality management, and excellence models in higher education were used as theoretical frameworks. There were three standards used: the Colombia decree 1330 of 2019, the ISO 9001 standard, and the Colombian Agreement 1 of 2020, which establishes the accreditation factors for higher education in Colombia. The results compared their characteristics and requirements. This allowed defining common processes and factors that guarantee the basic structure of an integrated quality management system while generating value for education programs. It is concluded that the ISO 9001 standard provides process management, innovation, and knowledge management. © 2021. All Rights Reserved.